Gym candy - Deuker, Carl, 1950- (Houghton Mifflin, 2007)
Groomed by his father to be a star player, football is the only thing that has ever really mattered to Mick Johnson, who works hard for a spot on the varsity team his freshman year, then tries to hold onto his edge by using steroids, despite the consequences to his health and social life.